Geodynamic processes in the NW Bohemian swarm earthquake region, Czech Republic, identified by continuous gas monitoring. Issue 3 (21st March 2013) - Weinlich, F. H.; Stejskal, V.; Teschner, M.; Poggenburg, J.
Abstract The time series of two continuously operating gas monitoring stations at Oldřišská and Nový Kostel located along seismoactive faults in the epicentral area of the NW Bohemian swarm earthquakes (Czech Republic) are compared with water level fluctuations in two boreholes positioned along these faults and with gas flux variations of a mofette at the Soos mofette field at 9 km distance. The seasonal trend of the monitored CO2 concentration with a maximum in November and a minimum in March/April is governed by groundwater temperatures, superimposed in spring by soil temperatures. CO2 concentration variations identified at Oldřišská are also reflected in gas flux variations in the Soos mofette and/or water level fluctuations of two boreholes. Variations in the gas monitoring recordings of station at Nový Kostel are also linked with variations at Oldřišská. In all data sets, diurnal variations generated by earth tides occur, reflecting a daily stress – fault permeability cycle. Additional stress interferes with this cycle. Significant, abrupt changes are attributed to geodynamic processes linked with seismic events, as revealed by local seismicity or by the transient of waves of a strong remote earthquake. Simultaneous variations of the gas concentrations in the Nový Kostel area and in the gas flux in the Soos point to an interconnected hydraulic conductive fault systems present in the northern part of the Cheb Basin. Sharp falls in gas concentration, during or subsequent to, earthquake swarms may reflect fault compression associated with impeded gas migration. However, gas variations also occur in periods without seismic activity, indicating changes in fault permeability were caused by local aseismic fault movements, as revealed by events with opposite trends in the gas recordings at Oldřišská, Nový Kostel and the Soos. Therefore, a mathematical approach to establish a correlation between seismicity and gas geochemical variations is not possible.